PENINGKATAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL SCRAMBLE DALAM PEMBELAJARAN IPS DI SEKOLAH DASAR - Pramesti, Widya Aldiena; Sugiyono, Sugiyono; Rosnita, Rosnita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract:General problem, how to improve student learning outcomes by using scramble in learning IPS class IV SD Negeri 03 Pontianak City?. This study aims to improve students' learning outcomes by using Scramble  in Social Science lesson class IV in SD Negeri 03 Pontianak City.The purpose in this reseasch composed by planning, implementation, observation and reflection. Subject in this research is teacher and students of grade IV A, which amounts to 36 students. Data collection techniques used by direct observation techniques and document data analysis techniques with data collections tool is observation sheet and sheet ultilizatiom and analysis of document data. The research result is (1) the ability of teacher planning of lesson in cyle I is 3.58, cyle II is 3,72, cyle III is 3.88. (2) the ability of teacher in implementation lesson in cyle I is 3.55, cyle II is 3.61, cyle III is 3.83, (3) the learning outcomes of student in cyle I is 68.78, cyle II is 78.97 and cyle III is 89. So, that can be concludes there is an improve the ability in planning, implementation, and learning outcomes in Social Science lesson by model scramble. Keyword :Improve, Learning Outcomes, and Model Scramble